2019
DOI: 10.3390/jcm8050713
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Remote Ischemic Preconditioning Conducted in Living Kidney Donors on Renal Function in Donors and Recipients Following Living Donor Kidney Transplantation: A Randomized Clinical Trial

Abstract: Although remote ischemic preconditioning (RIPC) has been shown to have renoprotective effects, few studies have assessed the effects of RIPC on renal function in living kidney donors. This study investigated whether RIPC performed in living kidney donors could improve residual renal function in donors and outcomes in recipients following kidney transplantation. The donors were randomized into a control group (n = 85) and a RIPC group (n = 85). The recipients were included according to the matched donors. Serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 41 publications
0
20
0
1
Order By: Relevance
“…In one multicentre, international trial 51 , RIPC decreased the incidence of delayed graft function (secondary outcome), and at 5-year follow-up there was a sustained improvement in eGFR after RIPC immediately before surgery compared with that in controls ( P = 0.004) (primary outcome) 57 . Another trial 56 reported that creatinine levels were increased significantly in the donor control group at discharge ( P = 0.003), and donors with high creatinine levels at discharge had a higher prevalence of chronic kidney disease after 1 year ( P = 0.003) (both secondary outcomes).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In one multicentre, international trial 51 , RIPC decreased the incidence of delayed graft function (secondary outcome), and at 5-year follow-up there was a sustained improvement in eGFR after RIPC immediately before surgery compared with that in controls ( P = 0.004) (primary outcome) 57 . Another trial 56 reported that creatinine levels were increased significantly in the donor control group at discharge ( P = 0.003), and donors with high creatinine levels at discharge had a higher prevalence of chronic kidney disease after 1 year ( P = 0.003) (both secondary outcomes).…”
Section: Resultsmentioning
confidence: 99%
“…Live-donor renal transplantation and the effects of RIPC were investigated in four trials 51–53 , 56 that measured estimated glomerular filtration rate (eGFR), creatinine concentration, urinary volume, levels of serum cystatin C, plasma neutrophil gelatinase-associated lipocalin (NGAL), urinary neutrophil gelatinase-associated lipocalin, urinary retinol-binding protein (RBP), urinary N -acetyl- d -glucosaminidase, and urinary liver-type fatty acid-binding protein, and outcomes in relation to graft function and rejection. One trial 56 also investigated the incidence of chronic kidney disease 1 year after surgery in donors, according to the Kidney Disease Improving Global Outcomes criteria. Another trial 51 assessed changes in tissue pathology.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, Bang et al. investigated whether RIPC performed in living kidney donors using a blood pressure cuff placed on upper arm (3 cycles of inflation to 200mmHg for 5 minutes followed by deflation of the cuff for 5 minutes) could improve kidney function and outcomes in both donors and recipients; serum creatinine levels for donors at discharge was significantly lower in donors who received RIPC, while no significant difference in serum creatinine, eGFR, risk for DGF, acute rejection and graft failure between the recipients of the two groups ( 135 ). Several pharmacological donor pre-treatments have been recently investigated in this setting.…”
Section: Strategies Of Interventionmentioning
confidence: 99%
“…24 A larger trial of 170 living kidney donor-recipient pairs with RIPC done on donors reported lower postoperative creatinine values on donors after RIPC but no long-term benefits for donors or recipients. 25 The largest kidney transplant RIPC trial to date, the REPAIR trial, showed that a RIPC performed in both donor and recipient immediately before a living-donor kidney surgery improved the estimated glomerular filtration for the whole follow-up period of 5 years. 26 27 The kidney allografts from living donors are subjected to very short ischaemia (in Finland this is typically less than 2 hours) and even greater benefits could be obtained if RIPC is performed in deceased donors, where ischaemia times are much longer (median 15 hours for kidney allografts in Finland, even longer in other countries).…”
mentioning
confidence: 99%